ANALYSIS OF REQUIREMENTS TO SYSTEMS SOFTWARE OF TESTING OF LEVEL OF KNOWLEDGES OF STUDENTS - Заміховський, Леонід Михайлович; Якубовський, Володимир Петрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this article facilities are considered co-operation between teacher and student at the controlled from distance method of teaching. The analysis of requirements is conducted to testing software of students knowledge level at the use both distance and traditional teaching.